A Damage Detection Approach for Cable-Stayed Bridges Using Displacement Responses and Mahalanobis Distance - Mahtab Mohseni Moghaddam; Ehsan Dehghani; Maryam Bitaraf (Journal of Rehabilitation in Civil Engineering)
Given the crucial role of cable-stayed bridges in infrastructure, continuous health monitoring throughout their lifespan is imperative. To achieve this purpose, a damage detection approach for cable-stayed bridges under loading was presented. This method aimed to assess the condition of cable-stayed bridges through phase space analysis of time domain responses. Displacement responses were utilized to minimize the need for extensive sensor deployment. Damage was identified by analyzing variations in the Mahalanobis distance index curve between intact and damaged models. This method was evaluated for effectiveness through a numerical case study. The case study involved damage design in the deck and cables of the Puqian cable-stayed bridge. The results demonstrated that this method can efficiently detect the damage location in the cable-stayed bridge and exhibited anti-noise capability in identifying the location of damage, especially for cables. Its accuracy at a noise level of 30 dB was 76.5%, 5.56%, and 75% for cable, deck, and combined cable and deck scenarios, respectively. This method can serve as a rapid and continuous monitoring tool for damage detection in cable-stayed bridges, with minimal traffic disruption and relying solely on deck displacement responses.